PELATIHAN PEMBUATAN NUGGET IKAN TUNA BAGI KELOMPOK MITRA DI DESA TANA TOA KECAMATAN KAJANG KABUPATEN BULUKUMBA - Alam, Roslina; Lantara, Niniek; Wahyuni, Nur (Arunika: Jurnal Pengabdian Masyarakat, 2022)
Indonesia as a Maritime Country has wider sea/water than its land area, one of the countries that has the largest fish content in the world. This extraordinary potential must be utilized to the fullest extent possible to improve the economy for the welfare of the people. The nutritional content of fish includes protein, carbohydrates, vitamins, minerals, and omega 3 fatty acids which have good benefits for the body. In addition, the nutritional content of fish is also much better when compared to foodstuffs derived from other proteins. So far, most fishermen or fish collectors only sell raw or salted fish, even though fish can be processed into a variety of products without reducing the nutritional value of fish. Diversification of processed fish will provide added value to processed fish products in addition to that the market will be wider both domestically and abroad because consumers have many choices. Processed fish products will be in demand by global consumers, if there is standardization and guarantee of safety and quality assurance for consumers, so that it can affect the increase in people's income. In the Community Partnership Program (PKM) they are not only taught how to process/cook, but also how to pack them properly and sell them to consumers. The participants also hope that this kind of activity will continue to be held on an ongoing basis so that it will become the basic capital to start selling fish, not only raw or semi-finished products, but contemporary ready-made products that are in great demand in the market, so that the ultimate goal is achieved, which is to increase their income. Fish nuggets are selected as a product that will be developed in this PKM. Other ingredients needed for fish nuggets, such as carrots and corn, are widely available in Bulukumba. Carrots and corn, can enrich the nutritional content of the nuggets, so that children and adults will be interested in consuming fish nuggets, which will lead to an increase in income health and community welfare